Oracula campbelli sp. n.—the first fossil darkling beetle (Coleoptera: Tenebrionidae: Alleculinae) from the late Eocene Rovno amber (Ukraine) - Nabozhenko, Maxim V.; Perkovsky, Evgeny E. (Zootaxa, 2023)
A new species of the currently Oriental alleculine genus Oracula Novák, 2019 is described from the Eocene Rovno amber, Ukraine: O. campbelli sp. n. This is the first report of a representative of the family Tenebrionidae from this Lagerstätte. Extant species of Oracula occur in Nepal, southern China (Yunnan), Thailand, Laos and Indonesia. The newly discovered extinct species is similar to extant O. amica Novák, 2019 from Nepal.